2017
DOI: 10.1177/2333794x17744141
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Association With Body Mass Index and Lipid Levels in Hispanic American Adolescents

Abstract: In this retrospective study, vitamin D deficiency was examined with body mass index (BMI) and lipid levels in a sample of Hispanic American adolescents. The prevalence of vitamin D deficiency among 234 subjects aged 13 to 19 years was 27.8%. Vitamin D deficiency was significantly associated with a BMI of 85 kg/m2 or higher (odds ratio = 2.02, 95% confidence interval = 1.11-3.69, χ2 = 5.37, P = .021), and 55.6% of the sample were overweight or obese (BMI ≥ 85%). In the overweight or obese subjects, vitamin D de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
5
28
1
Order By: Relevance
“…Their results presented that overweight and obese adolescents comprised 55.6% of the study sample and 33.9% of them were vitamin D deficient. The overweight or obese subjects in this sample were twice as likely to be vitamin D deficient as the underweight or healthy weight subjects [35]. This may be interpreted in the context of the fact that vitamin D insufficiency and excessive fat accumulation have mutually negative effects (i.e., the adipose tissue has an influence on the metabolism of vitamin D on the one hand, and its pathogenic role in the obesity development mechanisms on the other hand).…”
Section: Discussionmentioning
confidence: 83%
“…Their results presented that overweight and obese adolescents comprised 55.6% of the study sample and 33.9% of them were vitamin D deficient. The overweight or obese subjects in this sample were twice as likely to be vitamin D deficient as the underweight or healthy weight subjects [35]. This may be interpreted in the context of the fact that vitamin D insufficiency and excessive fat accumulation have mutually negative effects (i.e., the adipose tissue has an influence on the metabolism of vitamin D on the one hand, and its pathogenic role in the obesity development mechanisms on the other hand).…”
Section: Discussionmentioning
confidence: 83%
“…A negative correlation between vitamin D level and body mass index (BMI) has been described in literature (O'Dell et al, 2002;Rovner et O'Brien, 2008;Anonymous, 2014;Bani-issa et al, 2017;Elizondo-Montemayor et al, 2017;Hajjaj-Hassoun et al, 2017;Kumaratne et al, 2017). For example, Bani-issa et al (2017) found that in patients with BMI of 30 kg/m 2 or more, there was a risk of more than five times for vitamin D deficiency than for patients with BMI below 25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that patients with SCD are at risk of multiple macro-and micronutritional deficiencies, and they have a higher prevalence and risk of VDD regardless of their age or ethnic background [10][11][12]. Several studies have explored the risk factors influencing vitamin D status, such as limitation of exposure to natural light, which affects vitamin D biosynthesis; dark skin, which acts as a natural barrier to UV irradiation penetrating the skin; obesity and high body mass index, in which adipose tissues sequester vitamin D; and poor dietary intake of vitamin D [13][14][15].…”
Section: Introductionmentioning
confidence: 99%